(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3NHQ SJbGHGO ai CjGe YHO Gdedc hhdGjI GdMLGO Hf jhSa Hf GdMce GHf CHj Ybjd GdYQGbi (B: (3MMOKfi YHGS Hf gTGe Cf HTQ Hf eQhGf gdc HGdHUQI hgh Ydi GdchaI hGdHUQI s
(3BNQgG (B:s
(3hGYLHkG dgPG GdMeGQ GdfgGb HjfG gh jVQH CYfGbfG HGdCeS JbQHkG Edi Hfi CejI , EP QCi efge fHhI hCUGHJg LahI Ke bGd COYhce Edi CdSfI GdChGH ef GdSfI Cf JLYd QLdGg ai bjO hjLYd MjK LYdg YeQ HGdCeS Je GdLRA GdSGHY s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs